Effects of the Plasma-Activated Water on the Quality and Preservation of Fresh-Cut Lettuce - Chamorro, Juan Camilo; Denoya, Gabriela Inés; Santamaría, Brenda; Fina, Brenda; Ferreyra, Matías; Rodriguez, Anabel; Vaudagna, Sergio Ramon; Prevosto, Leandro (IEEE, Institute of Electrical and Electronics Engineers, 2023)
The effect of the application of plasma-activated water (PAW) on the quality and preservation of fresh-cut lettuce is reported in this article. PAW was produced by using a liquid-cathode air discharge. The average (bulk) water temperature was kept at ∼ 22 ∘ C during the activation procedure and stored at 4 ∘ C for up to five days. The pH value, electrical conductivity, and concentrations of H 2 O 2 and NO −3 in liquid at day 1 were 2.81, 1492 μ S/cm, and 77.8 and 223.4 mg/L, respectively, with slight variations over the whole storage time. No measurable amounts of NO −2 were found. Twenty pieces of lettuce leaves were washed for 1 and 5 min in 1 L of PAW and stored for one and five days. PAW treatments were compared to tap water treatments. The lettuce samples were stored at 4 ∘ C and analyzed on days 1, 3, and 7. The chromatic parameter results suggest that PAW treatments significantly reduce the degradation of lettuce chlorophyll from day 3 of refrigerated storage. The lettuce firmness was not significantly modified. The microbiological results of aerobic mesophilic (RAM), enterobacteriaceae, and psychrotrophs populations have shown that lettuce treated with PAW after three days of storage exhibited the strongest inactivation efficiency. Psychrotrophs counts were maintained for up to seven days. Similar inactivation efficiencies were found regardless of the PAW storage time. PAW treatments also favored both the antioxidant capacity FRAP, ABTS, and DPPH, and the total phenolic contents of lettuce at day 7 of storage. // Resumen: En este artículo se informa el efecto de la aplicación de agua activada por plasma (PAW) sobre la calidad y conservación de la lechuga recién cortada. PAW se produjo utilizando una descarga de aire de cátodo líquido. La temperatura promedio del agua (a granel) se mantuvo a ∼ 22 ∘ C durante el procedimiento de activación y se almacenó a 4 ∘ C por hasta cinco días. El valor del pH, la conductividad eléctrica y las concentraciones de H 2 O 2 y NO −3 en líquido el día 1 fueron 2,81, 1492 μ S/cm y 77,8 y 223,4 mg/L, respectivamente, con ligeras variaciones durante todo el tiempo de almacenamiento. . No se encontraron cantidades mensurables de NO −2. Se lavaron veinte trozos de hojas de lechuga durante 1 y 5 min en 1 L de PAW y se almacenaron durante uno y cinco días. Los tratamientos con PAW se compararon con los tratamientos con agua del grifo. Las muestras de lechuga se almacenaron a 4 ∘ C y se analizaron los días 1, 3 y 7. Los resultados de los parámetros cromáticos sugieren que los tratamientos PAW reducen significativamente la degradación de la clorofila de la lechuga desde el día 3 de almacenamiento refrigerado. La firmeza de la lechuga no se modificó significativamente. Los resultados microbiológicos de poblaciones de mesófilos aeróbicos (RAM), enterobacterias y psicrotrofos han demostrado que la lechuga tratada con PAW después de tres días de almacenamiento exhibió la mayor eficiencia de inactivación. Los recuentos de psicrotrofos se mantuvieron hasta por siete días. Se encontraron eficiencias de inactivación similares independientemente del tiempo de almacenamiento de PAW. Los tratamientos PAW también favorecieron tanto la capacidad antioxidante FRAP, ABTS y DPPH, como el contenido fenólico total de la lechuga en el día 7 de almacenamiento.